Pengaruh Spindle Speed Dan Feed Rate Terhadap Pembentukan Burr Dan Keakurasian Dimensi Lubang Pada Material Kuningan Menggunakan Teknologi Micro-Drill Machining - Udink Aulia; Yusuf Zaini; Saiful Hadi Yullah (Jurnal Teknik Mesin Unsyiah, 2018)
Machining technology, especially for micro hole cutting cases is a challenge in the industrial world to supply for components that have micro dimensions. The purpose of this study was to measure dimensional accuracy (roundness) and burr formation in the part of the entrance and exit holes. The object of the material used is brass plate. Brass plates with a thickness of 0.5 mm will be drilled using a twist drill chisel 0.2 mm diameter made from tungsten carbide material. Spindle rotation speed varied is 14,000 rpm, 17,000 rpm, and 20,000 rpm. The variation in feed rate for each spindle rotation is 5 mm / min, 8 mm / min, and 10 mm / min. The hole from the results will be observed and measured using a stereo microscope. From the measurement results show that the size of the largest hole dimensions with a value of 0.217 mm is formed at a rotation of 14,000 rpm and a feed rate of 5 mm / min, while the smallest hole diameter with a value of 0.202 mm is formed at a rotation of 20,000 rpm and a feed rate of 10 mm / min. The highest entrance burr value of 0.050 mm was formed at a rotation of 17,000 rpm and a feed rate of 10 mm / min, while the lowest height of 0.038 mm occurred at a rotation of 14,000 rpm and a feed rate of 5 mm / min. The highest exit burr value of 0.077 mm was formed at a rotation of 17,000 rpm and a feed rate of 10 mm / min, while the lowest height of 0.032 mm was formed at a rotation of 14,000 rpm and a feed rate of 5 mm / min. The results of this research data conclude that the accuracy of the hole dimensions and burr formation becomes better as the spindle rotation value and machining feed rate increase.